Culturing Articular Cartilage Explants in the Presence of Autologous Adipose Tissue Modifies Their Inflammatory Response to Lipopolysaccharide. (12th November 2020) - Pearson, Wendy; Garland, Anna E. N.; Nixon, Ashley; Cant, John P.; Hurtig, Mark B.
Abstract : The purpose of the current study was to explore the effect of autologous adipose tissue on cartilage responses to lipopolysaccharide (LPS). We hypothesized that LPS elicits an inflammatory response in cartilage, and that response is augmented in the presence of adipose tissue. Furthermore, we hypothesized that this augmented inflammatory response is due, at least in part, to increased exposure of cartilage to adipose tissue-derived c3a. Porcine cartilage explants from market-weight pigs were cultured in the presence or absence of autologous adipose tissue for 96 hours, the final 48 hours of which they were stimulated with LPS (0 or 10  μ g/mL). Adipose tissue explants were also cultured alone, in the presence or absence of LPS. Media from all cartilage treatments was assayed for c3a/c3a des Arg, PGE2, GAG, and NO, and the viability of cartilage tissue was determined by differential fluorescent staining. Media from adipose tissue explants was assayed for c3a/c3a des Arg and PGE2 . LPS produced a significant increase in PGE2, GAG, and NO production when cartilage was cultured in the absence of adipose tissue. Coculture of adipose tissue prevented a significant increase in PGE2 in cartilage explants. There was no effect of adipose tissue on LPS-induced GAG or NO, but the presence of adipose tissue significantly reduced cell viability in LPS-stimulated cartilage explants. Adipose tissue explants from lean animals reduced inflammatory responses of cartilage to LPS via a c3a/c3a des Arg-independent mechanism and were associated with a significant decline in cell viability. Thus, contrary to our hypothesis, adipose tissue from lean animals does not augment the inflammatory response of cartilage to stimulation by LPS. The mechanism of modulatory effects of adipose tissue on LPS-induced increase in PGE2 and decline in chondrocyte viability requires further research but appears to have occurred via a mechanism that is independent of adipocentric c3a/c3a des Arg.